Pengaruh Postingan Instagram Akun @Inspirasikristen_ Terhadap Motivasi Religius Followers - Herlina, Ririn; Budhiharti, Tri Widya (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This research discusses the influence of Instagram posts from the @Inspirasikristen_ account on religious motivation based on the aspects of Frequency, Intensity, and Message Content. The aim of this research is to determine the extent of the influence of social media, specifically Instagram, through the @Inspirasikristen account, on the religious motivation of its followers.The approach used is quantitative with a causal method based on the philosophy of positivism. The theory used is the Uses and Effects theory by Sven Windahl. The population of this research is the followers of the @Inpirasikristen account, with the sample size determined using the Slovin formula, resulting in 100 respondents. The research results indicate that the religious motivation of followers of the @Inspiraskristen_ account has an influence of 44.4%, with the remainder influenced by other variables not included in this study.